Interfaith tolerance through the Media of Indonesian newspapers - Umi Halwati; Imam Alfi (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This research is motivated by the reality of the issue of tolerance which is inseparable from the mass media. In the era of information and technology, interfaith tolerance is carried out with the help of technology, namely communication mediated by the mass media. This is because the mass media participates in constructing the reality of tolerance that is presented in Indonesian society with various religions. The mass media arranges the reality of various events of tolerance to become a meaningful discourse.Method - The research method used is framing analysis as a method to dismantle how the media constructs reality. The research data was obtained through news articles about interfaith tolerance in the newspapers Kompas, Republika, and Media Indonesia in 2016-2017 as the primary data, and supporting books or books relevant to research studies as the secondary data. The analysis technique used was the analysis of Zondhang Pan and Gerald M. Kosicki's models per news text on Kompas, Republika, and Media Indonesia.Result - The results of the research show that there are two important things, namely the reality of events and the reality of the media. What is presented by the media is the reality of the media. The reality of the media is not something to be taken for granted because the media actively shapes the reality of interfaith tolerance. The reality of inter-religious tolerance as a sensitive issue is constructed in various ways among the newspapers Kompas, Republika, and Media Indonesia; Each of the Indonesian newspaper media contributes to building interfaith harmony and national integration; Regarding religious tolerance, Kompas framing: Indonesia is a tolerant and harmonious country amidst religious diversity. Republika: Muslims are tolerant people. Media Indonesia: tolerance in Indonesia is still maintained.Implications - The reality of tolerance in the media has implications for tolerance in people's lives, that religious differences are a reality, so their existence must be respected.Originality - This research analyzes interfaith tolerance referring to media framing.***Tujuan - Penelitian ini dilatarbelakangi oleh realita isu toleransi yang tidak terlepas dari media massa. Di era informasi dan teknologi, toleransi antar umat beragama dilakukan dengan bantuan teknologi, yaitu komunikasi yang dimediasi oleh media massa. Pasalnya, media massa ikut mengkonstruksi realitas toleransi yang dihadirkan masyarakat Indonesia dengan berbagai agama. Media massa menata realitas berbagai peristiwa toleransi menjadi wacana yang bermakna.Metode – Metode penelitian yang digunakan adalah analisis framing sebagai metode untuk membongkar bagaimana media mengkonstruksi realitas. Data penelitian diperoleh melalui artikel berita tentang toleransi antaragama di surat kabar Kompas, Republika, dan Media Indonesia tahun 2016-2017 sebagai data primer, dan buku atau buku pendukung yang relevan dengan kajian penelitian sebagai data sekunder. Teknik analisis yang digunakan adalah analisis model Zondhang Pan dan Gerald M. Kosicki per teks berita di Kompas, Republika, dan Media Indonesia.Hasil - Hasil penelitian menunjukkan bahwa ada dua hal penting yaitu realitas peristiwa dan realitas media. Apa yang disajikan oleh media adalah realitas media. Realitas media bukanlah sesuatu yang bisa diterima begitu saja karena media secara aktif membentuk realitas toleransi antaragama. Realitas toleransi antar umat beragama sebagai isu sensitif dikonstruksikan dengan berbagai cara di antara surat kabar Kompas, Republika, dan Media Indonesia; Setiap media surat kabar Indonesia berkontribusi dalam membangun kerukunan antar umat beragama dan integrasi bangsa; Terkait toleransi beragama, Kompas membingkai: Indonesia adalah negara yang toleran dan rukun di tengah keberagaman agama. Republika: Umat Islam adalah umat yang toleran. Media Indonesia: Toleransi di Indonesia masih terjaga.Implikasi - Realitas toleransi di media berimplikasi pada toleransi dalam kehidupan masyarakat, bahwa perbedaan agama adalah sebuah realitas, sehingga keberadaannya harus dihormati.Orisinalitas - Penelitian ini menganalisis toleransi antaragama yang mengacu pada framing media.